Variations in carbon-to-phosphorus ratios of two Australian strains of Cylindrospermopsis raciborskii. Issue 3 (3rd July 2017) - Willis, Anusuya; Posselt, Amanda J.; Burford, Michele A.
Abstract: The toxic cyanobacterium Cylindrospermopsis raciborskii can form large blooms in freshwater systems, causing water quality problems. The availability of the essential macronutrient phosphorus (P), has a big impact on bloom formation but the variation in physiological response of different strains of C. raciborskii to available P has not previously been examined. This study investigated the carbon:phosphorus (C:P) ratio of two toxic Australian strains of C. raciborskii, AWT205 and NPD, under a range of P concentrations in batch and continuous cultures. P was added as a single dose to batch cultures and in continuous cultures at P concentrations of 0.032, 0.16, 0.64 and 16 μmol P l −1 . Cellular carbon and phosphorus content of both strains increased under P-limited conditions (0 μmol P l − 1 addition) with zero growth. Strain NPD had a lower C:P ratio (34:1) than AWT205 (150:1) indicating higher P storage capacity, and strain NPD survived P-limited conditions for longer. There was no significant difference in exponential growth rates (0.2 d − 1, P ≥ 0.5) under all P concentrations for both strains, with the exception of no P, demonstrating non-P-limited growth even at the lowest concentration (0.032 µmol P l − 1 ) and no increase in growth rate with additional P. 33 P uptake measurements were used to show that these strains both have very low half saturation constants (Ks = 0.02 μmol P l − 1 ) compared with other phytoplankton and strains of C. raciborskii . This is indicative of high uptake affinities and suggests that these strains are highly adapted to a low P supply. Overall the results of this study are consistent with the P strategy of storage prioritization over growth rate, and demonstrate differences between the strains in the C:P ratio under P-limitation, indicating variation in P storage.